A trial of three non‐invasive blood pressure monitors compared with invasive blood pressure assessment in atrial fibrillation and sinus rhythm. Issue 12 (10th September 2019) - Eysenck, William; Ammar, Ahmed; Kanthasamy, Vijaya; Freemantle, Nick; Veasey, Rick A.; Patel, Nikhil R.; Furniss, Stephen S.; Sulke, Neil
SUMMARY: Objective: To investigate the accuracy of three non‐invasive blood pressure (BP) devices in atrial fibrillation (AF) compared with invasive arterial BP. Methods: One hundred patients aged 45‐90 years, 63% male (50 in AF and 50 age matched controls in sinus rhythm [SR]) were identified with arterial lines measuring beat‐to‐beat BP fluctuation. Non‐invasive BP measurements utilising the manual sphygmomanometer (MS), PulseCor R6.5 (PC) and automated sphygmomanometer (AS) were taken simultaneously with invasive BP in a randomised sequence. This was repeated three times in each patient. Results: In SR differences in systolic BP (SBP) for MS, AS and PC were −0.34 mm Hg (95% CI −2.31 to 1.63; P  = .733), −3.80 mm Hg (95% CI −5.73 to −1.87; P  = .0001) and −3.90 mm Hg (95% CI −5.90 to −1.90; P  = .0001) and for diastolic BP (DBP) were 6.02 mm Hg (95% CI 4.39‐7.64; P  < .0001), 8.95 mm Hg (95% CI 7.36‐10.55; P  < .0001) and 7.54 mm Hg (95% CI 5.89‐9.18; P  < .0001), respectively. In AF mean differences in SBP for MS, AS and PC were −7.33 mm Hg (95% CI −9.11 to −5.55; P  < .0001), −5.29 mm Hg (95% CI −7.08 to −3.50; P  < .0001) and −5.75 mm Hg (95% CI −7.54 to −3.96; P  < .0001) respectively and for DBP were 5.28 mm Hg (95% CI 4.03‐6.54; P  < .0001), 6.26 mm Hg (95% CI 5.00‐7.52; P  < .0001) and 6.89 mm Hg (95% CI 5.64‐8.15; P  < .0001) respectively. Conclusions: The MS is accurate in SR because of direct assessment of Korotkoff sounds. Non‐invasive BP assessment in AF is significantly less accurate. These findings have important prognostic and therapeutic implications.